Analysis of disease profile, and medical burden by lead exposure from hospital information systems in China - Han Song; Jianchao Liu; Zipeng Cao; Wenjing Luo; Jing-Yuan Chen (BMC Public Health, 2019)
Abstract Background Though lead (Pb)-gasoline has been banned for decades in China, Pb continues to be a vital risk factor for various diseases. Traditional studies, without large sample size, were unable to identify explicitly the associations among Pb, its disease profile, and the related medical burden. This study was designed to investigate: 1) current status of blood Pb levels; 2) Pb-associated disease profile, medical burden, as well as impact factors. Methods Research subjects were patients who visited military hospitals and were required to test their blood Pb levels by doctors between 2013 and 2017. The large sample size and area coverage may, to a large extent, reveal the characteristics of Pb exposure in the whole Chinese population. Information of patients’ electronic medical records was extracted using Structured Query Language (SQL) in Oracle database. The spatial, temporal, and population distribution of their blood Pb levels were tested, to illustrate the association of Pb exposure with diseases’ profile, and medical burden. Non-parametric tests were applied to compare the differences of Pb levels among various groups. Results The blood Pb concentration showed a positively skewed distribution by Kolmogorov-Smirnov test (D = 0.147, p < 0.01). The blood Pb concentration of Chinese patients was 28.36 μg/L, with the lowest blood Pb levels, 4.71 μg/L, found in patients from Guangxi Zhuang Autonomous Region, and the highest, 50 μg/L, in Yunnan province. Han Chinese patients’ Pb levels were significantly lower than other minorities groups (z-score = − 38.54, p < 0.01). Average medical cost for Pb poisoning was about 6888 CNY for Chinese patients. Pb levels of patients with malignant neoplasm of lung, 45.34 μg/L, were far higher than malignant neoplasm of other respiratory, and intrathoracic organs, 24.00 μg/L (z-score = − 2.79, p < 0.01). Conclusions This study reported current status of blood Pb levels for patients who once visited military hospitals, partially representing the whole Chinese population. The result shows that Pb poisoning is still imposing marked economic burdens on patients under Pb exposure. Association of Pb with lung cancer may open up new areas for Pb-induced toxicology. The research strategy may advance toxicological studies in the aspect of medical data mining.